Pemikiran Politik Hasan Al-Banna & Implementasinya Terhadap Eksistensi Hukum Islam Modern - Yasin, Hendra (Qanuni : Journal of Indonesian Islamic Family Law, 2025)
This study aims to comprehensively examine Hasan al-Banna's Islamic political thought, especially regarding the integration of religion and politics in the Islamic government system and its relevance in the development of modern Islamic law. This study uses a qualitative method with a literature study approach, referring to Hasan al-Banna's primary works and secondary references from contemporary researchers. The results of the study show that the core of al-Banna's thought is rooted in the principle of monotheism as a source of sovereignty, shura as a mechanism for political participation, justice as the goal of government, and religious-political integration as the main foundation. This thought is relevant in responding to the renewal of Islamic law in Muslim countries, including Indonesia. Despite facing challenges such as secularism and legal pluralism, the opportunity for the actualization of al-Banna's thought remains open through strengthening the political awareness of the people, Islamic political education, and the development of contextual and adaptive contemporary ijtihad.